2013
DOI: 10.1371/journal.pone.0060323
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ion Gradients across Myocardial Ischemic Border Zones: A Biophysical Modelling Analysis

Abstract: The myocardial ischemic border zone is associated with the initiation and sustenance of arrhythmias. The profile of ionic concentrations across the border zone play a significant role in determining cellular electrophysiology and conductivity, yet their spatial-temporal evolution and regulation are not well understood. To investigate the changes in ion concentrations that regulate cellular electrophysiology, a mathematical model of ion movement in the intra and extracellular space in the presence of ionic, pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 188 publications
(206 reference statements)
0
23
0
Order By: Relevance
“…A very similar formalism was developed (in parallel) in the heart-cell community in the context of a model of ischemia [58]. Our buffering model accounted for electrodiffusive processes in the intra- and extracellular domain, and was essentially an expansion of the previous model by Qian and Sejnowski [64], which only considered the intracellular domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A very similar formalism was developed (in parallel) in the heart-cell community in the context of a model of ischemia [58]. Our buffering model accounted for electrodiffusive processes in the intra- and extracellular domain, and was essentially an expansion of the previous model by Qian and Sejnowski [64], which only considered the intracellular domain.…”
Section: Discussionmentioning
confidence: 99%
“…Along with other electroneutral models [5356, 58, 65], the KNP formalism provides a means of deriving the local potential V from the physical constraint that the (intra- and extracellular) bulk solution is electroneutral [28]. This approximation was used as early as in 1890 by Planck, who described electrodiffusion in electrolytes [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice represents a limitation, as the concentration of free calcium in rat plasma remains contentious. Previous studies have measured the extracellular free calcium concentration to be between 1 and 1.3 mM in rats (Moore, 1970;Polimeni, 1974) and the plasma concentrations of potassium to be between 3.3 and 5.8 mM, as reviewed in Niederer (2013 The interplay between calcium, TnC and tension generation is not included in our analysis and represents a limitation in our model. The inclusion of a sarcomere model with tension-dependent Ca 2+ buffering feedback would address this, albeit with a significant increase in model complexity.…”
Section: Limitationsmentioning
confidence: 99%
“…Lethal ventricular tachyarrhythmias during acute myocardial ischemia have been related to ST-T alternans due to repolarization and depolarization alternans and spatial heterogeneity of the APD restitution, and extracellular K + gradient across the ischemic border zone leading to systolic and diastolic injury current, and verapamil lessened the standard deviation of E K of the center and margin of ischemic myocardium during early stage of the ischemia. 14,21,22,23) We demonstrated that the ATP-sensitive K + channel opener pinacidil lessened the rise in extracellular K + during acute myocardial ischemia mainly by a marked decrease of the action potential duration of the ischemic myocardium. 24) Recently, intracoronary administration of verapamil and nicorandil, an ATP-sensitive K + channel opener, has been shown to be effective for the treatment of slow/no flow phenomenon in the acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 83%